The effect of Vaginal Ph on Ewes’ Fertility: Pengaruh Ph Vagina terhadap Kesuburan Sapi Betina - Hussein, Wathiq Faraon (Indonesian Journal on Health Science and Medicine, 2024)
Arabi ewes were used to determine the extent of the effect of the pH of the vaginal mucus on the fertility rate, vaginal sponges enriched with the progesterone hormone were used and the vaginas of the ewes were washed with different pH solutions. The fertility rate was 69.5%. There was no significant effect of the vaginal pH on this characteristic, and a positive correlation coefficient (0.821) was found between the two characteristics Highlights: Arabi ewes studied for vaginal mucus pH effect on fertility. Progesterone-enriched sponges, pH solutions used; fertility rate 69.5%. No significant effect, but strong positive correlation (0.821) found. Keywords: ewes, fertility, pH, buffers, phosphate